TELAAH HUKUM ISLAM TERHADAP PEMBERIAN DISPENSASI NIKAH DI INDONESIA - Erfan, Herfin Fahri (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2024)
Marriage dispensation is a legal solution for those who mostly do not yet have formal legal authority to marry. By taking the step of marriage dispensation, they are trying to ensure that their marriage can be legally recognized. This study analyzes differences of opinion among fiqh experts in determining age limits (baligh, ihtilam, rushd) which have implications for the right to consent in marriage. Marriage is prescribed in the Qur'an to realize the process of human regeneration. The desired generation is a generation of quality so that the task of living life is carried out based on the goals set by the Koran. This research aims to find out how the age limit for marriage in Islam is then analyzed by Islamic school scholars. Islam itself does not limit the ideal age for marriage. The jurists have different opinions regarding the age limit for marriage. The Shafi'i and Hanbali schools believe that the ideal age for marriage is 15 years, while Abu Hanifa believes that the age of maturity comes at 19 years for women and 17 years for men. Meanwhile, Imam Malik believes that the ideal age of maturity is 18 years for both men and women.